Design a new notched UWB antenna to rejected unwonted band for wireless communication - Ansam Qasim Kamil; Ali Khalid Jassim (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2021)
This paper presents a slotted design for ultra-wideband (UWB) antenna. Design of a rectangular UWB antenna covering the frequency range 3.1-10.6 GHz, to achieve notch characteristics in the bands at 3.1-8.4 GHz and 8.6-10.6 GHz. By changing the direction of distribution of current to apply this technique by inserting three C-shaped holes and two pairs of rectangular notches below the antenna. The simulation results reveal that the proposed structure is in good accord with the simulation results. The proposed UWB antenna size is (100x90x1.6 mm)3. This proposed design could provide a solution to eliminating bands that interfere in a UWB band depending on the aperture design. The simulated findings reveal that the UWB antenna operates in the 8.5 GHz center frequency range and rejects all frequency bands utilizing slits. This antenna design can provide a solution to remove UWB bands from 3.1-10.6 except for 8.5 GHz which only works. By using the notch, we got a large increase in the gain. makes to be a suitable candidate for X-band-UWB applications.